2019
DOI: 10.1002/poc.3999
|View full text |Cite
|
Sign up to set email alerts
|

Lack of resonance assistance in a classical intramolecular hydrogen bond: An exploration from quantum theory of atoms‐in‐molecules perspective

Abstract: A computational investigation has been performed to characterize the intramolecular hydrogen bond (IMHB) interaction in 7‐hydroxy‐2,3‐dihydro‐1H‐inden‐1‐one (7H1I). The results of natural bond orbital (NBO) analysis describe the formation of the IMHB in 7H1I in terms of hyperconjugative charge transfer from the lone electron pair of the acceptor oxygen atom (Oa) to the σ* antibonding orbital of the Od―H1 proton donating bond. However, the key motivation of the present work rests on characterization of the IMHB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
(189 reference statements)
0
1
0
Order By: Relevance
“…Many computational studies and experimental works can be found related to intramolecular and intermolecular RAHBs. The origin of the additional strength of RAHB as compared with conventional HBs is still a subject of an ongoing debate.…”
Section: Introductionmentioning
confidence: 99%
“…Many computational studies and experimental works can be found related to intramolecular and intermolecular RAHBs. The origin of the additional strength of RAHB as compared with conventional HBs is still a subject of an ongoing debate.…”
Section: Introductionmentioning
confidence: 99%